ABCC8-Related Maturity-Onset Diabetes of the Young (MODY12): A Report of a Chinese Family - Lin, Leweihua; Quan, Huibiao; Chen, Kaining; Chen, Daoxiong; Lin, Danhong; Fang, Tuanyu (Frontiers in Endocrinology, 2020)
Maturity-onset diabetes mellitus of the young (MODY) is a monogenic diabetes characterized by autosomal dominant inheritance. Its atypical clinical features make diagnosis difficult and it can be misdiagnosed as type 1 or type 2 diabetes. Fourteen subtypes of MODY have been diagnosed so far, of which MODY12 is caused by mutation of the ABCC8 (ATP Binding Cassette Subfamily C Member 8) gene, which is rarely reported in China. This paper reports a Chinese family of MODY12 caused by a rare missense mutation on the ABCC8 gene, which has not been reported to be associated with MODY in China or in other countries, with the aim of increasing clinicians' awareness and attention to the disease.